2003
DOI: 10.1108/01437730310485815
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of employees’ perceptions of knowledge sharing cultures

Abstract: This study investigated whether organizational factors such as employees’ perceptions of management’s support for knowledge sharing, their perceptions of the organization’s social interaction culture, the organization’s size, and the organization’s available knowledge sharing technology, as well as whether individual factors such as age, gender, and organizational tenure had a significant impact on employees’ perceptions of a knowledge sharing culture. New measures to assess employees’ perceptions of managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
515
2
16

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(556 citation statements)
references
References 16 publications
23
515
2
16
Order By: Relevance
“…Organizational size, together with the quality of the workforce, is considered a component of the human capital of the firm (Namasivayam and Denizci, 2006). Connelly and Kelloway (2003) demonstrated empirically a negative relationship between organizational size and knowledge sharing resulting from changes in social interactions. The following subsections review the effect of organizational unit size on four important factors that impact internal knowledge flows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizational size, together with the quality of the workforce, is considered a component of the human capital of the firm (Namasivayam and Denizci, 2006). Connelly and Kelloway (2003) demonstrated empirically a negative relationship between organizational size and knowledge sharing resulting from changes in social interactions. The following subsections review the effect of organizational unit size on four important factors that impact internal knowledge flows.…”
Section: Discussionmentioning
confidence: 99%
“…Trust, then, can be assessed on the basis of personal interaction, and is limited to a specific small group of people; the larger this group, the fewer personal relationships employees have established that impedes knowledge sharing (Connelly and Kelloway, 2003). Reputation can signal an assessment based on trust, made by others, as an indication of whether trust should be extended.…”
Section: Organizational Size and Knowledge Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Top management support is one of important variables that can affect organizational knowledge [29]. Numerous studies have found the importance of top management support for creating a climate that supports and provides sufficient resources [30], [31].…”
Section: Intellectual Stimulation and Knowledge Sharingmentioning
confidence: 99%
“…The first was to demonstrate that senior management was committed to the project and that all necessary actions had been authorised. As Connelly and Kelloway (2003) explain, this is a very important task because perceptions about management's support for knowledge sharing are potentially necessary for the creation and maintenance of a positive knowledge sharing culture in an organisation. They also agree with Martiny (1998) that uncertainty about leadership commitment to knowledge sharing is a key challenge in the deployment of KM.…”
Section: Building Strategic Relationships With the Workforcementioning
confidence: 99%